FAKTOR – FAKTOR YANG MEMPENGARUHI PENANAMAN MODAL ASING (PMA) DI ASEAN PERIODE 2000-2013 - Bambang H. Santoso; Made Siti Sundari; Idfi Setyaningrum (Jurnal Ekonomi dan Bisnis, 2015)
This research is giving a comprehension about some factors that could affect the Economic Growth using Endogenous Growth theory on countries in Association South East Asia Nation (ASEAN) in facing the ASEAN Economic Community (AEC) that will be open at the end of 2015. This research is using a linear regression model with panel data period of 2001-2013. Based on the Hausman test, the random effect model has been preferred over the fixed effect model. The findings chose 2 variables with the mot effect on Economic Growth, there are Human Capital-life expectancy (HKle), and Foreign Direct Investment (FDI). The choise of ASEAN has been made because there are very little research 2 about HK and FDI, and also because the major countries in this associaton are still in development countries